A study of the activity and effectiveness of recombinant fibroblast growth factor (Q40P/S47I/H93G rFGF-1) in anti-aging treatment - Żerańska, Justyna; Pasikowska, Monika; Szczepanik, Barbara; Mlosek, Krzysztof; Malinowska, Sylwia; Dębowska, Renata M.; Eris, Irena (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2016)
Introduction : Fibroblast growth factor 1 (FGF-1) is a powerful mitogen involved in the stimulation of DNA synthesis and the proliferation of a wide variety of cell types. Fibroblast growth factor 1 was genetically modified to improve its thermal stability and resistance to protease degradation without losing its biological activity. Aim : To study the impact of Q40P/S47I/H93G rFGF-1 on skin cells, its penetration through the skin and the evaluation of the rFGF-1-cosmetic product properties. Material and methods : In vitro studies included the examination of primary fibroblast and keratinocyte viability after the incubation with rFGF-1. The penetration abilities of rFGF-1 in various formulations and carrier systems were examined ex vivo by the Raman spectroscopy. In vivo studies – HF Ultrasound and 3D Imaging System – were used to evaluate the anti-aging properties of creams containing rFGF-1. Results : In vitro studies demonstrated that rFGF-1 strongly enhanced the viability of the treated cells. The Raman Spectroscopy analysis indicated that rFGF-1 encapsulated in lipid spheres penetrate through the stratum corneum to the depth of 60 μm, and added to the o/w formulation – could penetrate to a depth of 90 μm. The results obtained from Primos revealed the reduction of the volume and the depth of the wrinkles. Changes in the skin structure in the analyzed areas were evaluated by HF Ultrasonography. Conclusions : Recombinant FGF-1 strongly stimulated fibroblast and keratinocyte proliferation. However, the transition of this protein through the SC required an appropriate carrier system – lipid spheres. All tests – in vitro , ex vivo and in vivo – have proved that rFGF-1 is a substance with a potentially wide spectrum of use.